Differential Micronuclei Induction in Human Lymphocyte Cultures by Imidacloprid in the Presence of Potassium Nitrate - Polychronis Stivaktakis; Dimitris Vlastos; Evangelos Giannakopoulos; Demetrious P. Matthopoulos (The Scientific World Journal)
Humans are exposed to pesticides as a consequence of their application in farming or their persistence in a variety of media, including food, water, air, soil, plants, animals, and smoke. The interaction of pesticides with environmental factors may result in the alteration of their physicochemical properties. Square wave cathodic stripping voltammetry (SW-CSV), a technique that simulates electrodynamically the cellular membrane, is used to investigate whether the presence of potassium nitrate (KNO3) in the culture medium interferes with the genotoxic behavior of imidacloprid. The cytokinesis block micronuclei (CBMN) method is used to evaluate imidacloprid's genotoxicity in the absence or presence of KNO3 in the culture medium and, as a consequence, its adsorption by lymphocytes. Comparing micronuclei (MN) frequencies in control and imidacloprid-treated blood cell cultures, statistically significant differences were not detected. KNO3 did not induce MN frequencies compared to control. Statistically significant differences in MN frequencies were observed when blood cell cultures were treated with imidacloprid in the presence of increasing concentrations of KNO3. SW-CSV revealed that by increasing KNO3 molarity, imidacloprid's concentration in the culture medium decreased in parallel. This finding indicates that imidacloprid is adsorbed by cellular membranes. The present study suggests a novel role of a harmless environmental factor, such as KNO3, on the genotoxic behavior of a pesticide, such as imidacloprid. KNO3 rendered imidacloprid permeable to lymphocytes, resulting in elevated MN frequencies.